Meningkatkan Daya Saing Melalui Pemasaran Online Bagi Usaha Makanan Rajanya Jajanan Koenyaheun Bandung - Dita Amanah; B Lena Nuryanti; Clarissa Marza Zaidi; Dedy Ansari Harahap (Jurnal Pengabdian Masyarakat Waradin, 2025)
Koenyaheun is a small business in Bandung that sells food that has been established since 2010. Initial observation results indicate a need for online marketing assistance for this business. During the community service activities, several things were found including more online customers than customers who ordered directly from this business, word of mouth marketing and also the use of social media. Observations and interviews with business owners and employees were conducted to obtain information in this community service activity. Several problems were also found such as logos, product photos, packaging, marketing. Solutions to the problems have been conveyed to the business owner so that it is hoped that this business will gain greater profits and better future prospects. It is recommended to market products on various social media platforms such as Tokopedia, TikTok, Instagram, Facebook, YouTube, Twitter, WhatsApp or cooperation with food delivery service applications such as GrabFood, GoFood, ShopeeFood, so that they can reach a wider range of consumers.